IRPA Consultation: is the system of protection 'fit for purpose' and can it be readily communicated? Views of the radiation protection professionals. (23rd February 2018) - Coates, Roger; Czarwinski, Renate
Abstract: The system of protection, which provides the basic underpinning philosophy and principles for radiation protection, is constantly evolving in the light of developing scientific understanding and practical experience. Over recent times there has been significant learning from experiences relating to the Fukushima accident, and there is also increasing recognition of the importance of enhancing public understanding of radiation and risk. The practical application of radiation protection is undertaken by thousands of practitioners around the world, and it is IRPA's task to ensure that this experience is fed back for the benefit of all. This Memorandum reports the outcome of IRPA's consultation on the system of protection. The principal issues raised in the consultation include general perceptions of the system, risk uncertainties at low dose, the context of natural background exposure, dose limits and limitation, ALARA and reasonableness, and public understanding and communication of radiation and risk.